Beyond Punishment: Reformulating Corruption Law Enforcement for State Loss Recovery - Redy Handoko; Ikrar Demarkasi; Rudy Astanto; Slamet Haryadi; Viktoriya Melnykovych; Adi Sulistiyono (PT. Islamic Research Publiser, 2026)
The enforcement of corruption criminal law in Indonesia has predominantly emphasized punitive measures rather than the effective recovery of state financial losses. This orientation has generated significant challenges in achieving restorative justice, particularly in ensuring the return of assets lost through corruption offenses. This study aims to analyze the weaknesses of corruption law enforcement in the framework of state loss recovery and to formulate a more justice-oriented reconstruction of financial sanctions within corruption cases. The research employs a sociological juridical method with a descriptive-analytical approach. Data were obtained from primary and secondary legal materials, including statutory regulations, legal doctrines, court decisions, and field interviews with law enforcement actors. Data collection techniques involved literature review and interviews, while qualitative analysis was applied to interpret the findings systematically. The results reveal that weaknesses in corruption law enforcement arise from three interrelated dimensions: legal structure, legal substance, and legal culture. Structurally, the police face limited transparency in corruption case handling, the Corruption Eradication Commission (KPK) experiences constraints in investigating state-loss-oriented cases due to insufficient personnel, prosecutors remain hesitant in executing replacement money sanctions, and judicial disparities persist regarding subsidiary imprisonment for unpaid replacement money. Substantively, ambiguities within Article 18 paragraphs (2) and (3) of Law Number 20 of 2001 have weakened the effectiveness of financial recovery mechanisms. Culturally, persistent justificatory attitudes toward corruption continue to undermine legal compliance. This study contributes to the development of progressive anti-corruption law by proposing a reconstruction of financial sanction regulations through extending the payment period for replacement money and establishing clearer subsidiary imprisonment provisions to strengthen state asset recovery and achieve substantive justice.